Food Packaging Materials - Piergiovanni, Luciano; Limbo, Sara.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This Brief is concerned with the material chemistry of food packaging materials. It introduces the properties and peculiarities of typical packaging materials, such as plastics, cellulose components, ceramics and metals. Their overall performance as food packaging material is determined by the chemical and physical properties. The Brief describes how the final properties of a food packaging material can be influenced through chemical modifications in the structure and composition of the used components. The authors also cover potential chemical reactions of food packaging materials that may affect their performance. Potential hazards that may arise, such as influences on the product quality, or effects on their recycling or disposal, are discussed. Different influences, like metal corrosion, chemical resistance and degradability of the main packaging materials, or properties like hydrophobicity, surface energy and migration have to be taken into account. This Brief gives an introduction to all these different aspects of food packaging.
Introduction to Food Packaging Materials -- Ceramic Packaging Materials -- Metal Packaging Materials -- Cellulosic Packaging Materials -- Plastic Packaging Materials -- Materials Combination -- Chemical Features of Food Packaging Materials.
Keywords: Food science; Quality of life; Materials -- Analysis; Food Science; Quality of Life Research; Characterization and Analytical Technique